Study of Optimum Mix Design of Light-Weight Self Compaction Concrete (International Journal of Innovative Research in Computer Science & Technology, 2023)
The tremendous growth in population,  globalization and industrialization have led to the  development of the construction sectors. The construction  sector contributes a majorly to the development of the  country based on its infrastructural needs. Also, concrete  turns out to be the best and greatest construction building  material in the global scenario. Concrete has become a  highly sort out construction material because it could be  cast in-situ and precast satisfying the construction  feasibilities. The concrete is bifurcated into special types  of concrete for decades. One such special type includes  Self-Compacting Concrete (SCC). SCC has gained high  priority among other types of special concrete. SCC has  got a unique superior property of easy flowing nature.  The greatest credit of using SCC is that it is user-friendly  because it does not require compaction, consumes less  time, and provides a smooth surface and textured finish.  It does not require skilled labour. These advantages have  scored and drawn the attention of the construction sector.  Nowadays, most of the ready-mix plants use SCC to  serve their building. The findings from the current  investigation are summarized below. The workability of  concrete increase with the increase in the variation in the  partially replacement of cement with nano silica and  Coarse aggregate with the pumice light weight aggregate. The maximum compressive strength of M40 grade for 7  days of all the mixed combinations is found to be 38.88  N/mm2 when coarse aggregate was replaced with 36% by  pumice light weight aggregate and binder i.e., cement  with 0.8% by nano silica.The maximum compressive  strength M40 grade of concrete for 28 days of all the  mixed combinations is found to be 54.42 N/mm2 when  coarse aggregate was replaced with 36% by pumice light  weight aggregate and binder i.e., cement with 1.6% by  nano silica. The maximum split tensile strength M40 grade for 7 days of all the mixed combinations is found to  be 3.46 N/mm2 when coarse aggregate was replaced with  36% by pumice light weight aggregate and binder i.e.,  cement with 0.8% by nano silica. The maximum split  tensile strength M40 grade for 28 days of all the mixed  combinations is found to be 5.85N/mm2 when coarse  aggregate was replaced with 36% by pumice light weight  aggregate and binder i.e., cement with 1.2 % by nano  silica respectively. The maximum flexural strength M40  grade for 7 days and 28 days of all the mixed  combinations is found to be 6.78 N/mm2& 9.24 N/mm2 respectively. when coarse aggregate was replaced with  36% by pumice light weight aggregate and cement with  1.6 % by nano silica respectively. By using of waste  materials such as pumice light weight aggregate and nano  silica in concrete the structure becomes light weight and  economical and environment can be also protected for  pollution etc.
Keywords: Nano Silica; Pumice Light Weight Aggregate; Slump Test; Compression Test; Flexural Test Split Tensile Test